The Relationship of Knowledge and (Fathers’) Smoking Habits with the Incidence of Pneumonia in Toddlers in the Working Area of Penengahan Community Health Center, South Lampung, 2025 - Mia Yunita; Nur Sefa Arief Hermawan; William Arisandi (Universitas Ibn Khaldun Bogor, 2026)
Pneumonia remains one of the leading causes of mortality among children worldwide, including in Indonesia. One of the contributing factors to the high incidence of pneumonia in children is the low level of knowledge among parents and the prevalence of smoking habits, especially among fathers within the household. This study aimed to examine the relationship between fathers’ knowledge and smoking habits with the incidence of pneumonia in toddlers in the working area of the Penengahan Health Center, South Lampung Regency, in 2025. This research employed a quantitative design with a cross-sectional approach. The study population included all fathers of toddlers diagnosed with pneumonia within the Penengahan Health Center service area. A purposive sampling technique was applied to select respondents, and data were collected using a structured questionnaire that had been tested for validity and reliability. The data analysis consisted of univariate and bivariate methods, with the chi-square test used to determine the significance of relationships. The results revealed a significant association between the level of fathers’ knowledge and the incidence of pneumonia in toddlers (p-value < 0.05). Similarly, there was a significant relationship between fathers’ smoking habits and the occurrence of pneumonia in toddlers (p-value < 0.05). In conclusion, this study highlights that both knowledge and smoking behavior of fathers are significantly related to the incidence of pneumonia among toddlers. The findings emphasize the importance of continuous education and health counseling programs directed at parents, particularly fathers, to increase awareness, improve knowledge, and reduce smoking behavior in the household. Strengthening these preventive efforts is expected to contribute to reducing the burden of pneumonia in young children.